The technical delusion : electronics, power, insanity - Sconce, Jeffrey, 1962- (Duke University Press, 2019)
Delusions of electronic persecution have been a preeminent symptom of psychosis for over two hundred years. In 'The Technical Delusion' Jeffrey Sconce traces the history and continuing proliferation of this phenomenon from its origins in Enlightenment anatomy to our era of global interconnectivity. While psychiatrists have typically dismissed such delusions of electronic control as arbitrary or as mere reflections of modern life, Sconce demonstrates a more complex and interdependent history of electronics, power, and insanity. Drawing on a wide array of psychological case studies, literature, court cases, and popular media, Sconce analyzes the material and social processes that have shaped historical delusions of electronic contamination, implantation, telepathy, surveillance, and immersion. From the age of telegraphy to contemporary digitality, the media emerged within such delusions to become the privileged site for imagining the merger of electronic and political power, serving as a paranoid conduit between the body and the body politic. Looking to the future, Sconce argues that this symptom will become increasingly difficult to isolate, especially as remote and often secretive powers work to further integrate bodies, electronics, and information.